Pengaruh Pusat Logistik Berikat, Insentif Fiskal dan Dwelling Time terhadap Efisiensi Biaya Logistik pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean A Tangerang tahun 2019 - I Gusti Nyoman Sumaardiyasa; Chairil Anwar Pohan (Jurnal Ilmu Administrasi Publik, 2021)
Indonesia's logistics costs are the highest, around 24% of GDP based on World Bank studies. The aforementioned conditions are the cause of the sub-optimal performance of the national logistics sector.This study is important to find empirical evidence regarding the factors that influence the high cost of logistics in Indonesia. There are several other factors that affect the high cost of logistics, including infrastructure, transportation, additional costs imposed by logistics service providers, information technology and regulations. The high cost of logistics in Indonesia is also influenced by warehousing, shipping and other supporting activities. This study aims to analyze the influence of bonded logistics centers, fiscal incentives and dwelling time, either partially or simultaneously, on logistics cost efficiency. This research uses an explanative quantitative approach, it is used to examine certain populations or samples, the sampling technique is generally carried out randomly, data collection uses research instruments, data analysis is quantitative / statistical in order to test predetermined hypotheses. The population and sample are business actors and investors engaged in the export-import sector. The analysis used in this research is correlation and regression, t test, F test and determination coefficient test.The results prove that (1) the Bonded Logistics Center has a positive and significant effect on the efficiency of logistics costs by 60.5%. This shows that the more PLBs built by the government, the more efficient the logistics costs will be. (2) Fiscal incentives have a positive and significant effect on the efficiency of logistics costs by 51.9%. This shows that the efficiency of logistics costs in Indonesia can be driven, among others, through the provision of fiscal incentives from the government. (3) Dwelling time has a positive and significant effect on logistics cost efficiency by 69.8%. This means that the faster the dwelling time at the port will reduce logistics costs so that it is more efficient. Simultaneously, Bonded Logistics Center, fiscal incentives and dwelling time together have a positive and significant effect on logistics cost efficiency by 88.6%. Thus it can be concluded that these three variables are very dominant actors in reducing logistics costs in Indonesia.